Personal Idenity without a Person or an Identity - Žalgirytė, Jolita (Problemos, 2014)
The paper argues that theories of psychological continuity destroy themselves from within due to insufficient and unreliable methodological assumptions, hence personal identity is left without a person and an identity. It is claimed that thought experiments, being a necessary methodological means for establishing the existence of persons, are both insufficient and unreliable. Two arguments are presented. First, thought experiments presuppose conceptual possibility of distinctness and separation of a person and a biological organism, but the direct application of such possibility is not reliable due to subjective description of the thought experiment and lack of independent arguments. Second, two different interpretations of the same thought experiment (the brain transplantation case) yield conceptually possible, albeit contrary and thus ontologically incompatible, conclusions.